A contabilidade ambiental como instrumento de gestão turística: o caso da hotelaria de Caxias do Sul - Genta, Maria Mônica Pereira (My University, 2014)
Massive tourism has caused negative impacts to the natural environment, forcing tourism related companies, specially hotels, to introduce actions for environmental protection into its management procedures. Environmental Accounting, as an instrument for evaluation and assistance to environmental management, can demonstrate and make public the adopted measures and the results reached with these practices. According to this aspect, based on the expectation of understanding sustainable development, a questionnaire from the Green Deal Program, used in Guatemala, has been applied, intending to demonstrate the environmental managerial practices used in five hotels in Caxias do Sul/Brazil.After measuring the environmental action in the selected hotels, that is, those with at least one hundred rooms, with the assistance of the indicators used by the mentioned program, the information has been transformed in an uniform data system. Based on the Environmental Accounting theory, a model of Management Related Balance of Environmental Practices (MBEP) has been prepared, from a qualitative point of view, where environmental debit and credit are brought up in the empirical investigation. The model demonstrates the results of the environmental performance researched on the selected hotels in Caxias do Sul/Brazil.
A massificação do turismo provocou impactos negativos ao ambiente natural, forçando as empresas integrantes do setor turístico, especialmente a hotelaria, a introduzir práticas de proteção ambiental aos seus procedimentos de gestão. A Contabilidade Ambiental, enquanto instrumento de avaliação e auxílio à gestão ambiental, pode evidenciar e divulgar as medidas adotadas e os resultados alcançados nessas práticas. Partindo desta premissa, e tendo como fundamentação teórica a perspectiva de entender o denominado desenvolvimento sustentável, foi utilizado o questionário proposto no Programa Green Deal adotado pela Guatemala, com o objetivo de evidenciar as práticas de gestão ambiental aplicadas em cinco hotéis de Caxias do Sul. Uma vez medida a atuação ambiental dos hotéis escolhidos, que configuram aqueles com capacidade superior a cem unidades habitacionais, com a ajuda dos indicadores propostos pelo citado programa, as informações foram transformadas em um sistema de dados uniformes. Com base na teoria da Contabilidade Ambiental, foi elaborado um modelo de Balanço Gerencial de Práticas Ambientais (BGPA), do ponto de vista qualitativo, no qual são evidenciados os ativos e passivos ambientais identificados na investigação empírica. O modelo demonstra os resultados do desempenho ambiental dos hotéis pesquisados em Caxias do Sul.
Keywords: Turismo; Turismo e sustentabilidade; Gestão ambiental na hotelaria; Contabilidade ambiental; Tourism and sustainability; Environmental management in hotels; Environmental Accounting; Hotelaria